Hubungan Motivasi Belajar dengan Prestasi Belajar Siswa pada Mata Pelajaran Ekonomi Kelas X (Sepuluh) di MA Al-Qurtubiyyah Nagrak Tahun Pelajaran 2016/2017 - Ahmad Riyadi; Sayyidia Shofara Alhanif (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2020)
ABSTRACT .This study aims to examine the relationship between student learning motivation and student learning Achievement in economic subjects class X (Ten ) at MA Al-Qurtubiyyah Nagrak Academic Year 2016/2017. To obtain “X” variable data "Learning Motivation" using questionnaires or quiesioners and to obtain variable data “Y” "Learning outcomes" using the test. The research method used in this study is quantitative associative. The number of samples used in this study were 33 students in class X (Ten ). Analysis of the data used is; the first prerequisite test is validity and reliability test and normality test. Both hypothesis tests use the correlational test. The results showed that there was a significant relationship between learning motivation and student learning Achievement in Class X (Ten) Economics Subjects at the MA 2016 Al-Qurtubiyyah Nagrak Academic Year. Evident from the correlation coefficient of r = 0.821 the level of relations is very high, while the price of r² = 0.674. This shows that 67.4% of the variations that occur in student learning Achievement are related to student learning motivation. Keywords: Learning Motivation, Student Learning Achievement